PENGARUH GREEN ACCOUNTING TERHADAP SUSTAINABLE DEVELOPMENT DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MEDIASI - Anisa Dian Medianawati; Nur Cahyonowati (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of green accounting on sustainable development with Corporate Social Responsibility (CSR) disclosure as a mediating variable. This study uses independent variables (green accounting), dependent variables (sustainable development), and mediating variables (CSR disclosure). The population used in this study were manufacturing and energy sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample was selected using the purposive sampling method and obtained 379 samples. The analysis techniques employed were regression analysis and path analysis, utilizing SPSS 25 software. The results of this study reveal that green accounting has a positive effect on sustainable development, green accounting has a positive effect on CSR disclosure, CSR disclosure has a positive effect on sustainable development, and CSR disclosure is able to mediate the effect between green accounting and sustainable development.